Wireless multipath video transmission: when IoT video applications meet networking-a survey - Bhering, Fabiano (2022)
Advances in video camera and wireless communication technology have enabled a variety of video applications over the Internet. However, meeting these applications' quality-of-service requirements poses significant challenges to the underlying network and has attracted significant attention from the networking research community. In particular, wireless multipath video transmission has been proposed as a viable alternative to deliver adequate performance to Internet video applications. This survey provides a thorough review of the current state-of-the-art in multipath video transmission focusing on IoT applications. We introduce a taxonomy to classify existing approaches based on their application-specific mechanisms (e.g., video coding techniques) as well as networking-specific techniques. In addition to describing existing approaches in light of the proposed taxonomy, we also discuss directions for future work.